Fishing with copper acetylides: Selective alkynylation of heteronucleophiles. Issue 47 (22nd November 2018) - Guissart, Céline; Luhmer, Michel; Evano, Gwilherm
Abstract: Copper acetylides are readily available and especially convenient reagents for the alkynylation of a broad range of heteronucleophiles. Upon simple activation with molecular oxygen in the presence of suitable ligands and solvents, they readily transfer their alkyne moiety at room temperature, notably yielding a variety of nitrogen- and phosphorus-substituted alkynes. We report in this manuscript an extensive study of the chemoselectivity of this alkynylation based on quantitative 13 C NMR analyses. With suitable ligand/solvent combinations, various phosphorus-based nucleophiles can be alkynylated with excellent levels of selectivity, even in the presence of a large excess of a nitrogen-nucleophile. This chemoselective alkynylation could be further extended to an even more challenging selective alkynylation of a nitrogen-nucleophile over another one, further highlighting the synthetic potential of copper acetylides as alkynylating agents that can selectively "fish" a nucleophile without affecting others. Graphical abstract: